(untitled) (Fiep Bulletin - online, 2016)
The study of recycling is extremely important at the present time the country due to the increasing production of waste. Not only just the sorting of waste and its proper disposal, it is necessary and urgent, which are ways to reduce the volume of solid waste generated in Brazil. It is in this area that this study develops, looking for ways to solve this issue through recycling. But not only the recycling itself, which is made after the collection and disposal end of the waste, but rather take advantage of the waste solids directly from your source generating in order to reduce the costs of waste collection in Brazil and avoid their impacts on the environment and population throughout its transportation and subsequent disposal in landfills. For this, this paper aims to analyze new views on ways of recycling, with innovative ideas for the use of recyclable materials and the creation of new products from these materials. This research used documentary collections through information sources and also the bibliographic reference. The result achieved is expressed by a greater understanding of the possibility of reducing the generation of waste through innovative recycling ideas, reverse logistics policy and also the transformation of view of society on waste, promoting it as an opportunity generator. In conclusion, it follows that it is possible to reduce the generation of waste, just a joint effort of the public and public officials for Brazil to have a sustainable economic development.